125k views
0 votes
Tan(A—B)=tanA—tanB/1+tanAtanB​

User Fahmy
by
5.7k points

1 Answer

10 votes

Answer:

tan (A−B)=tan(A)−tan(B)/1+tan(A)tan(B)

tan(A−B)=tan(A)−tan(B)/1+tan(A)tan(B)

1+tan(A)tan(B) To prove this, we should know that:

1+tan(A)tan(B) To prove this, we should know that:sin(A−B)=sin(A)cos(B)−cos(A)sin(B)

1+tan(A)tan(B) To prove this, we should know that:sin(A−B)=sin(A)cos(B)−cos(A)sin(B)AND

1+tan(A)tan(B) To prove this, we should know that:sin(A−B)=sin(A)cos(B)−cos(A)sin(B)ANDcos(A−B)=cos(A)cos(B)+sin(A)sin(B)

1+tan(A)tan(B) To prove this, we should know that:sin(A−B)=sin(A)cos(B)−cos(A)sin(B)ANDcos(A−B)=cos(A)cos(B)+sin(A)sin(B)We start with:

1+tan(A)tan(B) To prove this, we should know that:sin(A−B)=sin(A)cos(B)−cos(A)sin(B)ANDcos(A−B)=cos(A)cos(B)+sin(A)sin(B)We start with:tan(A−B)=sin(A−B)/cos(A−B)

cos(A−B)tan(A−B)=sin(A)/cos(B)−cos(A)sin(B)cos(A)cos(B)+sin(A)sin(B)(1)

cos(B)−cos(A)sin(B)cos(A)cos(B)+sin(A)sin(B)(1)We would want to divide both numerator and denominator by cos(A)cos(B)

cos(B)−cos(A)sin(B)cos(A)cos(B)+sin(A)sin(B)(1)We would want to divide both numerator and denominator by cos(A)cos(B)but there are 4 cases,

  • cos(B)−cos(A)sin(B)cos(A)cos(B)+sin(A)sin(B)(1)We would want to divide both numerator and denominator by cos(A)cos(B)but there are 4 cases,cos(A)=0 and cos(B)≠0
  • cos(B)−cos(A)sin(B)cos(A)cos(B)+sin(A)sin(B)(1)We would want to divide both numerator and denominator by cos(A)cos(B)but there are 4 cases,cos(A)=0 and cos(B)≠0cos(A)≠0 and cos(B)=0
  • cos(B)−cos(A)sin(B)cos(A)cos(B)+sin(A)sin(B)(1)We would want to divide both numerator and denominator by cos(A)cos(B)but there are 4 cases,cos(A)=0 and cos(B)≠0cos(A)≠0 and cos(B)=0cos(A)=0 and cos(B)=0
  • cos(B)−cos(A)sin(B)cos(A)cos(B)+sin(A)sin(B)(1)We would want to divide both numerator and denominator by cos(A)cos(B)but there are 4 cases,cos(A)=0 and cos(B)≠0cos(A)≠0 and cos(B)=0cos(A)=0 and cos(B)=0cos(A)≠0 and cos(B)≠0

cos(B)−cos(A)sin(B)cos(A)cos(B)+sin(A)sin(B)(1)We would want to divide both numerator and denominator by cos(A)cos(B)but there are 4 cases,cos(A)=0 and cos(B)≠0cos(A)≠0 and cos(B)=0cos(A)=0 and cos(B)=0cos(A)≠0 and cos(B)≠0The question on this page is asking for specific formula, which comes from Case 4, so I will only solve Case 4 here.

cos(B)−cos(A)sin(B)cos(A)cos(B)+sin(A)sin(B)(1)We would want to divide both numerator and denominator by cos(A)cos(B)but there are 4 cases,cos(A)=0 and cos(B)≠0cos(A)≠0 and cos(B)=0cos(A)=0 and cos(B)=0cos(A)≠0 and cos(B)≠0The question on this page is asking for specific formula, which comes from Case 4, so I will only solve Case 4 here.Dividing numerator and denominator in (1) by cos(A)cos(B) we get:

cos(B)−cos(A)sin(B)cos(A)cos(B)+sin(A)sin(B)(1)We would want to divide both numerator and denominator by cos(A)cos(B)but there are 4 cases,cos(A)=0 and cos(B)≠0cos(A)≠0 and cos(B)=0cos(A)=0 and cos(B)=0cos(A)≠0 and cos(B)≠0The question on this page is asking for specific formula, which comes from Case 4, so I will only solve Case 4 here.Dividing numerator and denominator in (1) by cos(A)cos(B) we get:tan(A−B)=sin(A)/cos(B)−cos(A)/sin(B)/;2cosA)cos(B)/cos(A)cos(B)+sin(A)sin(B)/cos(A)cos(B)

cos(A)cos(B)tan(A−B)=sin(A)cos(B)/cos(A)cos(B)−cos(A)sin(B)cos/(A)cos(B)cos/(A)cos(B)co(A)cos(B)+sin(A)sin(B)/cos(A)cos(B)

cos(A)cos(B)tan(A−B)=sin(A)/cos(A)−sin(B)cos(B)1+sin(A)cos(A)sin(B)cos(B)

cos(A)−sin(B)cos(B)1+sin(A)cos(A)sin(B)cos(B) tan(A−B)=tan(A)−tan(B)/1+tan(A)tan(B)

Explanation:

Hope it is helpful....

User Osama Sayed
by
5.2k points